Bypass pigging technology on amelioration of pigging-induced liquid flow: An experimental and modelling study. (15th February 2020) - Chen, Jianheng; He, Limin; Luo, Xiaoming; Lu, Lin; Zhang, Hailong; Li, Xiaowei; Liu, Haixiao; He, Songtao
Abstract: Liquid overflow accident during pigging operation in offshore oil and gas field inevitably leads to production loss and deferment, which could be effectively addressed by applying bypass pigging technology. Aiming to analyze amelioration effects of pigging-induced liquid flow through bypass pigging, the paper first conducted a gas-liquid two-phase bypass pigging experiment, then developed a CFD bypass pigging model to investigate the downstream liquid slug dissipation mechanism. Furthermore, a surge liquid volume analytical model was established to conduct parametric analysis. The results show that bypass pigging could ameliorate pigging-induced liquid accumulation, achieving a much smaller terminal pressure oscillation. Attributed to the gas-liquid carrying effect, the increase in bypass fraction from 0% to 2% reduces liquid outflow rate up to 75%, achieving a more manageable liquid arrival profile. Downstream liquid slug dissipation hinges on the balance between force of the pig exerting on the liquid and gas-carrying effects, which could be effectively enhanced by an increased gas-liquid relative velocity. Pig velocity dominates the surge volume. By combining bypass pigging technology and increasing liquid drain rate, the liquid overflow accident could be potentially avoided. The study lays a solid foundation for the advancement of bypass pigging technology in offshore oil and gas fields.